Effect of Self-Care Guidelines on Symptoms Burden for Patients with Lung Cancer Undergoing Chemotherapy - Asmaa M. E. Elsayed; Ola A. Ahmed; Asmaa H. Mohamed; Fatma M. Mahrous; Diaa Eldean M. Sherif (Evidence-Based Nursing Research)
Context:  Lung cancer is common cancer worldwide. Because of the high-symptoms burden and severe morbidity, effective symptoms management requires comprehensive self-care strategies.